2019
DOI: 10.1016/j.jddst.2019.101166
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin loaded vascular prostheses functionalized with poly-methylbeta- cyclodextrin: The importance of in vitro release conditions

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Trotta et al have reported the good performances and the versatility of their nanosponges [56]. Besides, our team has reported the same properties of our poly(cyclodextrin citrate) toward triclosan [39], ciprofloxacin [40], simvastatin [46], ethoxzolamide [57].…”
Section: Study Of the Interactions Between Ibu And Pcd In Solutionsupporting
confidence: 69%
See 2 more Smart Citations
“…Trotta et al have reported the good performances and the versatility of their nanosponges [56]. Besides, our team has reported the same properties of our poly(cyclodextrin citrate) toward triclosan [39], ciprofloxacin [40], simvastatin [46], ethoxzolamide [57].…”
Section: Study Of the Interactions Between Ibu And Pcd In Solutionsupporting
confidence: 69%
“…where K f (L/g) is the Freundlich constant and 1 n is the relative adsorption capacity characteristic [40].…”
Section: Ibuprofen Sorption and Isotherms Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…CDs have a truncated cone-shaped 3D structure. They have a hydrophobic cavity that can form inclusion complexes with a large variety of lipophilic molecules and that can work as a drug carrier in sustained release drug delivery systems [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Promising results have been reported with CHT/CDP/metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Garcia-Fernandez et al [ 166 ] developed polyester vascular grafts modified with polymerised M-β-CD and loaded with ciprofloxacin to prevent postoperative infections. The release of ciprofloxacin from the prostheses without poly-M-β-CD was faster than from the M-β-CD functionalised prostheses, regardless of the flow rate, indicating the superiority of poly-M-β-CD in the controlled, sustained release of ciprofloxacin.…”
Section: Modern Drug-delivery Systemsmentioning
confidence: 99%